TIME-RESOLVED OPTICAL SPECTROSCOPY AND PHOTOMETRY OF THE PEOULIAR POLAR BY CAM (=H0538+608) - Somova, T. A.; Somov, N. N.; Bonnet-Bidaud, J. M.; Monchet, M. (Одеські астрономічні публікації, 2017)
Results of simultaneous spectral and photometric observations of the pecular polar BY Cam in the high state of brightness (V =14m.2- 15m.6) obtained in February 1990 and March 1991 at the 6-rn telescope of SAO RAS are presented.